Respuesta :

helox

Answer:

d=-2 c=-3

Step-by-step explanation:

3c-8d=7

4(c+2d=-7)

3c-8d=7

4c+8d=-28

4c+3c-8d+8d=7-28

7c=-21

c=-3

c+2d=-7

-3+2d=-7

2d=-4

d=-2

Given.

[tex](3c-8d=7)=(c+2d=-7)[/tex]

Multiply 4 to the second equation.

[tex]4(c+2d=-7)[/tex]

[tex]3c+8d=-28[/tex]

Compare the like terms.

[tex]4c+3c-8d+8d=7-28[/tex]

Solve.

[tex]7c=-21[/tex]

Divide 7 to both sides

[tex]\frac{7c}{7}=\frac{-21}{7}[/tex]

[tex]c=-3[/tex]

Substitute (-3) for c into the original second equation.

[tex]c+2d=-7[/tex]

[tex]-3+2d=-7[/tex]

Add (3) to both sides.

[tex](-3+2d=-7)+3[/tex]

[tex]2d=-4[/tex]

Divide (2) to both sides.

[tex]\frac{2d}{2}=\frac{-4}{2}[/tex]

[tex]d=-2[/tex]

Check your work.

[tex]3(-3)-8(-2)=7[/tex]

[tex]-9+16=7[/tex]

[tex]7=7[/tex]

[tex]c+2d=-7[/tex]

[tex]-3+2(-2)=-7[/tex]

[tex]-3-4=-7[/tex]

[tex]-7=-7[/tex]

Therefore your answer is.

[tex]c=-3\\d=-2[/tex]